“The Weather [to]Day”: Overexposure To and Of the Media in Kenneth Goldsmith’s Work - Hélène Aji (Sillages Critiques)
Over the span of nine books and some fifteen years, Kenneth Goldsmith, now in his forties, living in New York and working in Philadelphia, unfolds what he calls in turn a poetics of uncreativity and a poetics of boredom. Each text draws from the quotidian in its most minute details to produce text that is either borrowed and collaged or simply transcribed. Boring and uncreative, these are the qualities Goldsmith claims for all these works and others, putting into question the demands of originality and interest that underlie the canon of poetry. This paper interrogates the denial of originality which in actuality initiates a highly original (and ironic) poetic practice.